Sponsored versus non-sponsored initial public offerings stock market performance : Evidence from the Nordic markets from 2005 to 2017 - Kuoppamäki, Henri (My University, 2019)
The purpose of this study is to investigate the magnitude of underpricing and long-run performance of Nordic initial public offerings. The sample used in the study contains 135 IPOs on the Copenhagen, Helsinki, Oslo, and Stockholm Stock Exchanges issued between January 2005 and December 2014. The sample includes 28 private equity-backed, 22 venture capital-backed, and 85 non-sponsored IPOs. The study has been focusing on the differences in underpricing and long-run aftermarket performance between these IPO groups. The scope was to find evidence that the sponsored IPOs, i.e., private equity- or venture capital-backed IPOs are less underpriced and perform better than non-sponsored IPOs in the long-run by evaluating their 36-month performance in the stock markets. Also, the underpricing and long-run performance are explored depending on the sizes of the firms and market conditions at a time of issuance. I find the evidence of underpricing in all groups in the Nordic sample, but the results are moderate compared to previous research. In contrast to previous research, private equity-backed IPOs experience higher first-day returns than other IPOs. When exploring the aftermarket performance, I find that the private equity-backed and non-sponsored IPOs outperformed the benchmarks over the long-run period. Private equity-backed IPOs had superior performance compared to its counterparts in 36 months, and surprisingly the VC-backed IPOs performed worst in the same time regime.
Keywords: IPO, Initial Public Offering, Private Equity, Venture Capital, listautumisanti